(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This theoretical study aimed to provide reflections about the contributions of the Theory of Social Representations (TSR) to the approach of upcycling in ​​Fashion. The theoretical foundation is based on the conceptual elements of upcycling and TRS. The cut of the article is defined by the literature review on two topics, seeking to show its articulation. The literature shows the relationship of upclycling as sustainable development, in contrast to what is meant by “recycling”. In the psychosocial perspective of the TSR, as the subjects / groups elaborate representations about upclycling, mainly in the fashion area, it indicates an understanding of meanings that are constructed through communication, exposing specific interests and revealing cultural identities. The article seeks to awaken reflections that can support future empirical studies, since issues related to sustainability are increasingly present in training and in the world of fashion work, and the understanding of the meanings constructed by the various groups involved becomes relevant in this context.